COMPARATIVE STUDY OF PERFORMANCE BASED BEHAVIOUR OF MOMENT RESISTING FRAMES WITH STRUCTURAL SHEAR WALLS, CONCENTRIC BRACED FRAMES & BUCKLE RESISTING BRACED FRAMES - Baig, Mirza Amir; Rehman, Adeeb Ur (International Journal of Research -GRANTHAALAYAH, 2020)
Performance evaluation and design of civil facilities against earthquakes is a challenge to engineers because of the large uncertainty in the seismic demand and capacity of structures. The purpose of the study is to perform comparative analytical investigation of performance-based behavior between Moment Resisting Frames with Structural shear Walls, Concentric Braced Frames & Buckle Resisting Braced Frames of a concrete structure by using ETABS-2017 software. The comparative analytical evaluation of the study will be based on the parameters such as displacement, inter-story drift, pushover curve and life expectancy level. The purpose of the study is to obtain a structural system which is more efficient, reliable and strong in its nature and strength.